2022
DOI: 10.1097/ijg.0000000000002163
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Clinician Acceptance of a Deep Learning-Based Clinical Decision Support Tool for Predicting Glaucomatous Visual Field Progression

Abstract: Précis: We updated a clinical decision support tool integrating predicted visual field (VF) metrics from an artificial intelligence model and assessed clinician perceptions of the predicted VF metric in this usability study. Purpose: To evaluate clinician perceptions of a prototyped clinical decision support (CDS) tool that integrates visual field (VF) metric predictions from artificial intelligence (AI) models. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…They found that while their interface was revealed to show mediocre usability (SUS score in the 43rd percentile, mean ± SD SUS score = 66.1±16.0), earlier work has shown that clinicians commonly have unfavorable perceptions of EHR usability when estimated using SUS scores (mean scores < 10th percentile). This highlights the challenges of developing usable CDS instruments in the EHR and the demand for continuous work in this area 71 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that while their interface was revealed to show mediocre usability (SUS score in the 43rd percentile, mean ± SD SUS score = 66.1±16.0), earlier work has shown that clinicians commonly have unfavorable perceptions of EHR usability when estimated using SUS scores (mean scores < 10th percentile). This highlights the challenges of developing usable CDS instruments in the EHR and the demand for continuous work in this area 71 …”
Section: Resultsmentioning
confidence: 99%
“…70 These instruments are a reliable way to evaluate user satisfaction with DL models and to assess the cognitive and time burden a model imposes. 70 Chen et al 71 recently applied one of these tools, the SUS score, to calculate a commonly used and validated scoring system that ranges from 0 to 100 for evaluating the user-friendliness of the GLANCE interface. They found that while their interface was revealed to show mediocre usability (SUS score in the 43rd percentile, mean ± SD SUS score = 66.1 ± 16.0), earlier work has shown that clini cians commonly have unfavorable perceptions of EHR usability when estimated using SUS scores (mean scores < 10th percentile).…”
Section: Decision Support To Minimize Time and Cognitive Burden On Usersmentioning
confidence: 99%
See 1 more Smart Citation